Treatment of combined etiology gingival smile: case report - Smaniotto, Lilian Aline; Moreno, Sandriane; Nuernberg, Marta Aparecida Alberton (Revista Uningá, 2023)
The smile’s aesthetics is the source of self-esteem and it has a fundamental role in society. Excessive gingival exposure when smiling is a recurring aesthetic complaint in the dentist’s office. Gummy smile is defined as gingival exposure greater than three mm from the gingival margin to the upper lip line during spontaneous smile. The gummy smile has several etiologies, which can be alone or in combination. The treatment to be used depends directly on the etiological factor. The present case report aims to present a therapeutic option for a gummy smile of combined etiology, resulting from vertical maxillary excess, upper lip hypermobility and altered passive eruption. The proposed treatment involves the application of botulinum toxin type A in the elevator lips superioris muscles and the clinical crown augmentation. The therapeutic approach of choice is a less invasive option with satisfactory results. The recognition of the etiology of gummy smile guides the choice of treatment method and it ensures an adequate clinical result, returning aesthetics and self-esteem to the patient.